(untitled) (Modern education and development, 2025)
The topic “Classification of Affixes According to Various Criteria” explores the systematic categorization of affixes—morphemic units attached to roots or stems—in English. It focuses on different classification principles such as position in word structure (prefixes, suffixes, infixes, circumfixes), function in part-of-speech transformation (e.g., nominal, verbal, adjectival affixes), origin (native vs borrowed), semantic contribution (e.g., negation, intensity, repetition), and usage (productive vs non-productive). Understanding these classifications is essential for studying word formation, enriching vocabulary, and analyzing morphological processes in English linguistics.